Is there really a debris disc around ζ2 Reticuli?. Issue 1 (25th August 2018) - Faramaz, V; Bryden, G; Stapelfeldt, K R; Booth, M; Bayo, A; Beust, H; Casassus, S; Cuadra, J; Hales, A; Hughes, A M; Olofsson, J; Su, K Y L; et al.
ABSTRACT: The presence of a debris disc around the Gyr-old solar-type star $ζ ^2\, Reticuli\, $ was suggested by the Spitzer infrared excess detection. Follow-up observations with Herschel /PACS revealed a double-lobed feature that displayed asymmetries both in brightness and position. Therefore, the disc was thought to be edge-on and significantly eccentric. Here we present ALMA/ACA observations in Band 6 and 7 which unambiguously reveal that these lobes show no common proper motion with $ζ ^2\, Reticuli\, $ . In these observations, no flux has been detected around $ζ ^2\, Reticuli\, $ that exceeds the 3σ levels. We conclude that surface brightness upper limits of a debris disc around $ζ ^2\, Reticuli\, $ are $5.7\, \mathrm{μ Jy\, arcsec^{-2}}$ at 1.3 mm, and $26\, \mathrm{μ Jy\, arcsec^{-2}}$ at 870 microns. Our results overall demonstrate the capability of the ALMA/ACA to follow-up Herschel observations of debris discs and clarify the effects of background confusion.